2013
DOI: 10.1080/13562576.2013.817512
|View full text |Cite
|
Sign up to set email alerts
|

European Union Cross-Border Cooperation and Conflict Amelioration

Abstract: The relevance of European Union (EU) cross-border cooperation for European border conflict amelioration may be questioned in the contemporary global climate of threat and insecurity posed by forces of 'dark globalisation'. In any case, empirical evidence exposes the limitations of cross-border cooperation in advancing conflict amelioration in some border regions. Nevertheless, in an enlarged EU which encompasses Central and East European member states and reaches out to neighbouring states through cross-border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The settlement patterns in the Jarso-Girhi territory and the profoundness of their socio-historical and economic interactions seem to permanently challenge the politics of ethnicity and the attempt to mould sharp definition of ‘binary distinctions between “self and other”, “us” and “them”, “here” and “there”, and “inside” and “outside”’ (McCall, 2013: 203). From the Gultangian peacebuilding perspectives (Galtung and Jacobsen, 2000), the Jarso-Girhi conflicts and identity-based violence being experienced in the area call for relational politics of place in which the relational ontology of spatiality is maintained and where places and boundaries that link them become ‘open, discontinuous, relational and internally diverse’ (Allen et al, 1998: 143).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The settlement patterns in the Jarso-Girhi territory and the profoundness of their socio-historical and economic interactions seem to permanently challenge the politics of ethnicity and the attempt to mould sharp definition of ‘binary distinctions between “self and other”, “us” and “them”, “here” and “there”, and “inside” and “outside”’ (McCall, 2013: 203). From the Gultangian peacebuilding perspectives (Galtung and Jacobsen, 2000), the Jarso-Girhi conflicts and identity-based violence being experienced in the area call for relational politics of place in which the relational ontology of spatiality is maintained and where places and boundaries that link them become ‘open, discontinuous, relational and internally diverse’ (Allen et al, 1998: 143).…”
Section: Discussionmentioning
confidence: 99%
“…That is why they made metaphorical elevation of their water wells as wives. Their metaphorical usage clearly revealed that in the context of territorial contestation what McCall (2013: 200) elegantly captures as ‘the potent brew of social, political, cultural and emotional forces’ is at work. For further details, see Adugna (2011) for insights on how the Boran who initially resisted against referendum-based resolution of territorial disputes finally decided to take part in the referendum to defend their contested territory and to maintain their strong symbolic, cultural and socio-political link to it.…”
mentioning
confidence: 99%
“…Challenges to cooperation may arise from national and international pressure (e.g. security issues, immigration control, the financial crisis) or from conflicting territorial logics advanced by regional and local actors (Popescu 2008;McCall 2013). In that way, borderlands themselves become the sources of conflict, defined by the type and goals of actors within them.…”
Section: Theoretical Framework: Borderlands Regionalist Parties and mentioning
confidence: 98%
“…But we do not know how this then resonates on the other side of the border. Especially lacking are enquiries into territorial issues related to cooperation and contention, including electoral competition, where the media facilitate or obstruct cross-border relations: By shaping imagined communities, including regional communities (Morley 2000), they may either enhance or smoothen controversies surrounding cross-border issues (McCall 2013). So although some scholars argue that the media tend to enhance national borders, for instance through stereotypes (e.g.…”
Section: Theoretical Framework: Borderlands Regionalist Parties and mentioning
confidence: 98%
“…Since its very inception, the project of European integration has been regarded as a prime symbol/example of debordering, unification and cooperation. Both symbolically and materially, it has worked to reconfigure hard borders into soft borders underpinned by intergovernmental cooperation among states, the development of multilevel governance and the support for various programs of cross-border cooperation (McCall 2013;Anderson and O'Dowd 1999;Scott 2012;Hayward et al 2011). Initially set against the backdrop of World War II, the suspension of borders as barriers and their divisive impact on international and inter-state relations has also essentially cast European integration as a project associated with conflict resolution and peacebuilding (McCall 2014).…”
Section: Cross-border Cooperation and Its Limits: Trademark Of Europementioning
confidence: 99%